Effect on composition and quantity of extracellular polymeric substances in an innovative hybrid membrane bioreactor under different sludge retention times. Issue 1 (1st January 2019) - Li, Ying; Chen, Wei; Liu, Qiang; Xiang, Wei; Zheng, Xing-Can; Qu, Ji-Xiang
ABSTRACT: This study investigated the influence of sludge retention time (SRT) in three hybrid membrane bioreactors to treat domestic wastewater at different SRTs (10, 20, and 40 d) simultaneously, based on extracellular polymeric substances (EPS) analysis. The results showed that significant positive correlation existed between SRT and humic acids quantity in TB-EPS, humic acids quantity in S-EPS, DNA quantity in S-EPS, and total quantity in TB-EPS, with the correlation coefficient 0.9992, 0.9980, 0.9973, 0.9821, respectively. Significant negative correlation existed in SRT and proteins in TB-EPS, proteins quantity in S-EPS, and polysaccharose in S-EPS, with the correlation coefficient 0.9993, 0.9107, 0.8552, respectively. A high logarithmic relationship existed between supernatant turbidity and SVI. The optimal SRT was 20 d and the corresponding operational cycle of the membrane module was 109 d.